2001
DOI: 10.1046/j.1365-2249.2001.01671.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin D on the growth of normal and malignant B-cell progenitors

Abstract: SUMMARYAs the effects of vitamin D 3 , 1,25-dihydroxyvitamin D 3 (1,25-(OH) 2 -D 3 ) (VD, calcitriol) on the proliferation and differentiation potential of normal and leukaemic cells in vitro of myeloid lineage are known, we investigated the response to VD on the growth of both normal and malignant lymphoid progenitors. Effects of vitamin D on normal human lymphoid progenitors and B lineage acute lymphoblastic leukaemia (ALL) progenitors were assessed by using an in vitro cell colony assay specific for either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 46 publications
2
14
0
2
Order By: Relevance
“…30 The expression of these molecules on PEL cells was confirmed by immunohistochemical staining (Figure 4).…”
Section: Identification Of Genes Specifically Expressed By Pelmentioning
confidence: 78%
See 1 more Smart Citation
“…30 The expression of these molecules on PEL cells was confirmed by immunohistochemical staining (Figure 4).…”
Section: Identification Of Genes Specifically Expressed By Pelmentioning
confidence: 78%
“…First, cross-linking of the adhesion molecule PSGL-1 has been described to inhibit proliferation of hematopoietic stem cells, 43 implying a potential functional role for this surface receptor also in the control of cell proliferation. Second, because it has been suggested for other vitamin D 3 receptor-positive B-cell malignancies, 30 activation through the vitamin D 3 receptor exposed on PEL cells might induce differentiation of the tumor cells and potentially contribute to treatment. Third, PEL tumor cells express mucin-1, a tumorassociated antigen that might represent a suitable target for antibody-mediated therapy.…”
Section: Pel-specific Genesmentioning
confidence: 99%
“…In another type of NHL, DLBCL, treatment of the cell line models with calcitriol and vitamin D analogs induced necrosis . Calcitriol also inhibits growth of malignant B cell progenitors from ALL, while leaving viability and differentiation state unchanged .…”
Section: Vitamin D Effects On Malignant Hematological Cellsmentioning
confidence: 99%
“…In addition, Antony et al [] showed that 1,25D had no effect on lymphoblastic leukemia cell proliferation, and actually had a modest effect of impairing dexamethasone cytotoxicity and induction of apoptosis. On the contrary, Consolini et al [] reported significant inhibition of the growth of normal and malignant lymphoid progenitors by 1,25D, despite lack of detectable VDR expression on leukemic blast cells, suggesting a leukemia cell‐extrinsic function of 1,25D in regulating leukemogenesis. Considering the tightly controlled yet multifactorial variability in these in vitro experiments, further detailed investigations into leukemia cell‐intrinsic and ‐extrinsic effects of VDDs in the physiologically relevant in vivo setting of human malignancies and animal models are strongly warranted.…”
Section: Vitamin D and Malignanciesmentioning
confidence: 99%